The effect of acetazolamide on intracerebral hemorrhage in stoke patients - Abbasi, Vahid; Salimi, Maryam; Amani, Firouz (International Journal of Advances in Medicine, 2017)
Background: 10-20% of all strokes are caused by intracerebral haemorrhage which is the world's leading cause of neural tube defects and the second cause of mortality in the world. The aim of this study was to assessment the effect of acetazolamide in the symptom improvement, decreasing rankin scale and mortality rate in patients with intracerebral haemorrhage. Methods: This is a clinical trial study that has been done on 120 stroke patients which divided randomly in two groups each with 60 patients. Patients in intervention group take acetazolamide 750 mg/day and in control group take placebo. The status of patients investigated by Rankin scale in three times baseline, 72 hours and 3 weeks after Cerebral haemorrhage. Results: Of all patients, 49 (40.8%) were male and 71 (59.1%) were female. Putamen haemorrhage is the most location for cerebral haemorrhage (n = 43, 35.8%). According to the Rankin scale, 53 (44.2%) of patients were in the status 4 “moderately severe disability. Unable to attend to own bodily needs without assistance and unable to walk unassisted” in baseline. In the intervention group based on Rankin scale after 72 hour and three week the recovery rate was significantly more than control group. Conclusions: Acetazolamide can be effective in treatment haemorrhagic stroke, decreasing Rankin scale and mortality rate in patients with cerebral haemorrhage.